Certain Virtualities, The Physical Spaces of the Academic Library during and after the Learning-centered Paradigm Shift - Eriksson, Cecilia (My University, 2020)
Throughout the twentieth century, the primary responsibility for the academic library has been to provide access to their growing collection, but during the past decades this has changed. An increased number of students enrolled at higher education, alongside an exponential expansion of digitised material have created a springboard for the academic library to enter the beginning of a new era – the learning-centered paradigm. This master’s thesis aims to highlight what impacts the learning-centered paradigm shift have on the physical spaces of the academic library. The illustrative case of Linköping University Library exemplifies an academic library that has encountered the shift in two major steps, whereof the last involved the inauguration of Studenthuset in 2019. The motives and consequences of the study object is described and later fragmentised with support from observations made on site and in the floorplans and through an assortment of concepts put forth by Gilles Deleuze. Combined, the assorted concepts form a linear chain of events describing change, which supports the understanding of the conceptual intentions of the architect, alternative outcomes, and the general impacts of the learning-centered paradigm. The study shows that the idea of the learning-centered paradigm has been established but it is dependent on architecture, which is a slow field of knowledge, to spatially manifest it. The chance was given to the study object, but not fully taken. Instead, an academic library that in the future rather will be perceived as a hybrid library became the result. The main impact the learning-centered paradigm has on physical space is the risk of inscribing uncertainties into the building, which might evoke future intensities earlier than expected. It is not wrong to build during a paradigm shift, but it is of great importance to be aware of current tendencies.
Keywords: academic library, learning-centered paradigm, Studenthuset, Linköping University Library, virtualities, Gilles Deleuze, linear chain of events